2015
DOI: 10.1001/jamadermatol.2014.2694
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Knowledge Gap in Clinical Recommendations for Management and Complete Excision of Clinically Atypical Nevi/Dysplastic Nevi

Abstract: This consensus statement reviews the complexities of management of CAN/DN. A review of the literature and 2 rounds of a structured Delphi consensus resulted in the following recommendations: (1) mildly and moderately DN with clear margins do not need to be reexcised, (2) mildly DN biopsied with positive histologic margins without clinical residual pigmentation may be safely observed rather than reexcised, and (3) observation may be a reasonable option for management of moderately DN with positive histologic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…1 They note that, ''.observation may be a reasonable option for management of MDN with positive histologic margins without clinically apparent residual pigmentation; however, more data are needed to make definitive recommendations in this clinical scenario.'' 1 This conclusion is based on several studies that look at the clinical follow-up of MDN, including a small minority that showed histologically positive margins.…”
mentioning
confidence: 99%
“…1 They note that, ''.observation may be a reasonable option for management of MDN with positive histologic margins without clinically apparent residual pigmentation; however, more data are needed to make definitive recommendations in this clinical scenario.'' 1 This conclusion is based on several studies that look at the clinical follow-up of MDN, including a small minority that showed histologically positive margins.…”
mentioning
confidence: 99%
“…). All articles evaluated by the recent consensus statement by the Melanoma Prevention Working Group were among the articles that met inclusion criteria …”
Section: Resultsmentioning
confidence: 99%
“…To date no such trial has been conducted, and it is unlikely that one will be performed for this clinical question given costs. There has been a proposal by the Pigmented Lesion Subcommittee of the Melanoma Prevention Working Group of collecting multicentre prospective data regarding outcomes for observed vs. re‐excised dysplastic naevi . Hopefully with prospective studies such as these, higher quality retrospective cohort studies, uniform pathology reporting and long‐term outcomes analyses we will be able to have stronger evidence about what types of patients and associated histological features deem re‐excision vs. observation as the preferred intervention balancing both benefits and harms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study highlights the wide range of treatment suggestions for melanocytic lesions that lack national treatment guidelines. 23,24 Physician experience and training influenced whether pathologists made suggestions, with dermatopathology training trending towards more conservative treatment suggestions for mild and moderately dysplastic nevi. For melanomas and melanoma in situ, pathologists typically made treatment suggestions in accordance with the established NCCN guidelines.…”
Section: Discussionmentioning
confidence: 99%